Detoxificação de milho (zea mays L.) contaminado com aflatoxinas através do processamento por extrusão termoplástica - Mandarino, José Marcos Gontijo; Coelho, Dilson Teixeira; Gomes, José Carlos; Parreiras, June Ferreira Maia (Semina: Ciências Agrárias, 1989)
<!--[if gte mso 9]> Normal 0 21 MicrosoftInternetExplorer4 <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman";} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:35.4pt; mso-footer-margin:35.4pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> Experiments were conducted to study the efficiency of the thermoplastic extrusion process in reducing aflatoxin levels on naturally contaminated yellow dent corn. Quantification was accomplished by high performance liquid chromatography (HPLC). The extration method used was efficient, since recovery of added anatoxins B1, B2, G1 e G2 (10 ppb each) was 104,0; 102,7; 92,5 and 77,0% respectivaly. Subjecting contaminated yellow com flour samples at 35% moisture the thermoplastic extrusion process reduced aflatoxin B1, B2 and G2 levels below the FDA guideline of 20 ppb total aflatoxin.